Beyond donations: Isomorphism and revenue mix in nonprofit start-ups - Elizabeth Searing (Administrative Sciences, 2023)
The literature on nonprofit growth contains a practical ambiguity regarding which types of revenues to cultivate as a start-up nonprofit. The revenue portfolio of a more established organization may be inappropriate (or unattainable) for a new one, but there may be perils in relying too long on sources of nonprofit start-up capital. We posit that nonprofit entrepreneurs choose to mimic larger organizations in their field for growth rather than rely on the revenue mix of their start-up stage. This study uses two different dynamic econometric models to estimate the role of revenue type and other organizational factors in the growth of young and small nonprofits. We find that mimicking the revenue habits of larger organizations is generally (but not universally) advisable, with most conclusions sensitive to subsector.
Keywords: 350; dynamic modeling; growth; isomorphism; nonprofit; revenue management